2020
DOI: 10.3390/aerospace7060074
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Low-Thrust Orbit-Raising of All-Electric Satellites

Abstract: In this paper, we consider a recently developed formulation of the electric orbit-raising problem that utilizes a novel dynamic model and a sequence of optimal control sub-problems to yield fast and robust computations of low-thrust trajectories. This paper proposes two enhancements of the computational framework. First, we use thruster efficiency in order to determine the trajectory segments over which the spacecraft coasts. Second, we propose the use of a neural network to compute the solar array degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Electric propulsion has been used by NASA's Deep space 1 [1] and Dawn [2], ESA's SMART-1 [3], and JAXA's Hayabusa and Hayabusa 2 [4]. Electric propulsion systems have demonstrated that lowthrust engines can be used for long-duration travels by the planetary and interplanetary space missions [5]. Low-thrust electric propulsion spacecraft is known to have a greater payload capability than conventional chemical propulsion spacecraft.…”
Section: Introductionmentioning
confidence: 99%
“…Electric propulsion has been used by NASA's Deep space 1 [1] and Dawn [2], ESA's SMART-1 [3], and JAXA's Hayabusa and Hayabusa 2 [4]. Electric propulsion systems have demonstrated that lowthrust engines can be used for long-duration travels by the planetary and interplanetary space missions [5]. Low-thrust electric propulsion spacecraft is known to have a greater payload capability than conventional chemical propulsion spacecraft.…”
Section: Introductionmentioning
confidence: 99%